Curriculum Adaptation in Learning Student with Special Needs at Inclusive Schools Surakarta City - Istiqomah Putri Mirasandi (Indonesian Journal of Disability Studies, 2019)
The study aims to determine the ability of Special Assistance Teachers in adapting the curriculum for Children with Special Needs in inclusive schools. The research was carried out in Public Elementary School 1 of Pajang Surakarta. The research subjects were special companion teachers in inclusive schools. Data collection on the teacher's ability to adapt the curriculum using the interview method with special accompanying teachers and documentation methods regarding learning devices for children with special needs at school. The analysis technique uses qualitative analysis of triangulation models from Miles and Huberman. This analysis model consists of three stages, namely the stage of data reduction, data presentation, and conclusion. The results of the study showed that most of the special assisting teachers had not been able to adapt the curriculum, because some of the special assistant teachers were not graduates of Special Education. Special mentoring teachers need interventions to improve their competence in curriculum adaptation.